SWIPE UP TO GLOWING : STRATEGI JITU MARKETING CONTENT DAN INFLUENCER MARKETING DALAM MERAIH MINAT BELI KONSUMEN SKINCARE DI MEDIA SOSIAL - Reni Wulandari; Jessica Adela Anastasya Arnold; Michelle Couwandy; Muh. Sultan Amin Kevin Sariputra Niodilt; Erwin Erwin (LPPM STIE Muhammadiah Bandung, 2025)
The development of the skincare industry is currently increasingly rampant and has become a consumer need for consumers in maintaining their skin health. Its existence in the marketing world is currently trending because it follows the rapid development of digitalization by using social media as a medium to develop effective digital marketing. The purpose of this study is to analyze the influence of the contribution of Marketing Content and the effect of using Influencer Marketing in increasing consumer Buying Interest in skincare businesses on social media. This study used 250 respondents of skincare users in the city of Makassar, both women and men, by considering several deeper criteria related to Marketing Content in marketing skincare products and utilizing Influencer Marketing in marketing on social media. Data collection used a questionnaire based on a Likert scale with 5 scales. The data obtained were analyzed using the Partial Least Square–Structural Equation Model (PLS-SEM) and the data processing process used SmartPLS version 4. The results of this study indicate a positive and significant influence of the use of Marketing Content and Influencer Marketing on consumer Buying Interest in skincare on social media with target consumers in the city of Makassar. It can be stated that Marketing Content can contribute well to Influencer Marketing used by skincare businesses to increase consumer relationships and Buying Interest in the community towards skincare on social media.